Effect of sintering on the structure, microstructure and electrical properties of mechanosynthesized Y2O3 and Dy2O3 alloyed ceria nanoparticles: A comparative study. (December 2019) - Dutta, S.; Bandyopadhyay, S.; Dutta, A.; Pradhan, S.K.
Graphical abstract: Highlights: Structural parameters are estimated by Rietveld analysis. Sintering effect on the structural parameters are compared. Relative densities are measured and compared. Sintering effect on electrical properties of the compounds is investigated. Abstract: A comparative study of the effect of sintering temperature on the microstructure and electrical properties of Dy2 O3 (a rare earth oxide) and Y2 O3 (a non-rare earth oxide) alloyed CeO2 nanoparticles synthesized by mechanical alloying has been carried out. All structural and microstructural parameters of these CeO2 -based nanoparticles are estimated by analyzing the XRD patterns employing the Rietveld refinement method. FESEM images demonstrate the effect of sintering on the grain size and porosity of both these compounds and reveal the uniform and homogeneous distributions of elemental Ce, Dy, Y and O in two types of compound. In general, electrical conductivities of these compounds are found to increase with an increase in sintering temperature. In unsintered and at lower sintering temperatures the total conductivity value of Y2 O3 alloyed compound is less than that of Dy2 O3 alloyed compound and becomes higher when sintered at 1100 °C. Electrical relaxation is found to be thermally activated phenomenon for both these compounds. Effect of the sintering temperature on the relaxation time of both these compounds is compared and discussed.